Synoptic Parousia Parables and the Apocalypse - Bauckham, Richard (New Testament studies, 1977)
In the continuing discussion of the possible role of Christian prophets in the formation of the tradition of the words of Jesus, reference continues to be made to the relevance or irrelevance of the words of the exalted Christ transmitted by the prophet John in the Apocalypse. They remain the only un-disputed example from the first century of prophetic utterances made in the name of Christ in the first person, and for advocates of the creative activity of the Christian prophets they are therefore invaluable evidence that such utterances could be made. Their use as evidence for the role of prophecy in the formation of the Synoptic tradition involves, admittedly, additional assumptions not easily demonstrable. We must suppose that John's prophecy is typical of the content of early Christian prophecy in general, and also that this late first-century work is faithfully representative of the earlier prophets whom alone we can suppose to have been responsible for originating logia which actually entered the Synoptic tradition. The uniqueness of John's prophetic status vis-à-vis that of the church prophets has been cogently argued by D. Hill, and it seems that at least we cannot infer otherwise un-attested characteristics of early Christian prophecy in general from the contents of the Apocalypse alone. In any case the Apocalypse is surely untypical in being a lengthy and closely integrated literary composition, with its own distinctive stylistic traits. Partly for this reason the words of Christ reported in it are for the most part quite unsuitable for transference to the lips of the Jesus of the Synoptic tradition, at least without substantial adaptation.